2004
DOI: 10.1111/j.0022-2720.2004.01299.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase differentiation via combined EBSD and XEDS

Abstract: SummaryElectron backscatter diffraction (EBSD) and orientation imaging microscopy have become established techniques for analysing the crystallographic microstructure of single and multiphase materials. In certain instances, however, it can be difficult and/or time intensive to differentiate phases within a material by crystallography alone. Traditionally a list of candidate phases is specified prior to data collection. The crystallographic information extracted from the diffraction patterns is then compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 7 publications
0
53
0
Order By: Relevance
“…In the case of infinite dilation, this process is repeated until each point becomes a member of a grain. The cleaning operation was followed by grain confidence index [20] standardization. The grain CI-standardization cleaning method is used to match the CIs of all the points within a grain.…”
Section: B Oim Analysismentioning
confidence: 99%
“…In the case of infinite dilation, this process is repeated until each point becomes a member of a grain. The cleaning operation was followed by grain confidence index [20] standardization. The grain CI-standardization cleaning method is used to match the CIs of all the points within a grain.…”
Section: B Oim Analysismentioning
confidence: 99%
“…Further work [5] has shown that the use of electron backscattered diffraction (EBSD) can provide useful crystallographic information for these complex intermetallic phases. However, phase identification is not necessarily conclusive using either crystallographic information obtained using EBSD or chemical information using energy dispersive X-ray analysis (EDX) in isolation because of the similarities in both chemistry and crystal structure between the different multicomponent phases [6].…”
Section: Introductionmentioning
confidence: 99%
“…Quartz CPO and misorientation plots are based on quartz mineral orientation maps created using electron backscatter diffraction (EBSD) on polished sections of quartz veins (Nowell and Wright, 2004;Prior et al, 1999). Polished sections were mechanically polished to 0.3 ÎŒm grit and chemically polished with a colloidal silica suspension (Lloyd, 1987).…”
Section: Methodsmentioning
confidence: 99%